Collapse of medium-thick-walled pipes with multi-oval defects under external pressure. (15th August 2022) - Li, Tao; Xie, Peng; Li, Xiaotian
Abstract: For exploring the effect of axial factors of oval defect on pipes collapse, the FE model verified by experimental results is used to research the collapse response of medium-thick-walled pipes with multi-oval defects. The ultimate collapse mode of pipes is "dogbone" shape, whether the pipes with single or multi-oval defects in the axial direction or uniform oval pipes. The "dogbone" mode occurs in each maximum oval defect when oval defect spacing larger than 5 times the pipe diameter, while flip-flop mode when the defect deviation angle equals to 90°. Collapse pressure decreases as the oval defect or transition length increases; first increases and then decreases as the defect spacing increases; decreases as the difference of unequal ovality increases. The deviation angle between double oval defects can improve the anti-collapse pressure of pipes while increasing the number of oval defects has an almost negligible effect on collapse pressure. Improved collapse pressure formulas consider ovality and axial factors based on DNV specification formula are proposed to predict collapse pressure of pipes with single or multi-oval defects. The improved formulas show a correlate well with numerical and experimental results. Highlights: Collapse of medium-thick-walled pipes with single or multi-oval defects is studied by using verified FEM. The axial factors of oval defect effects on the collapse behavior of pipes are discussed. Improved collapse pressure formulas consider ovality and axial factors are proposed. The prediction pressure based on the improved formulas are correlate well with numerical and experimental results.